Heme oxygenase-1 attenuates acute pulmonary inflammation by decreasing the release of segmented neutrophils from the bone marrow - Konrad, Franziska M.; Braun, Stefan; Ngamsri, Kristian-Christos; Vollmer, Irene; Reutershan, Joerg (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2014)
Recruiting polymorphonuclear neutrophil granulocytes (PMNs) from circulation and bone marrow to the site of inflammation is one of the pivotal mechanisms of the innate immune system. During inflammation, the enzyme heme oxygenase 1 (HO-1) has been shown to reduce PMN migration. Although these effects have been described in various models, underlying mechanisms remain elusive. Recent studies revealed an influence of HO-1 on different cells of the bone marrow. We investigated the particular role of the bone marrow in terms of HO-1-dependent pulmonary inflammation. In a murine model of LPS inhalation, stimulation of HO-1 by cobalt (III) protoporphyrin-IX-chloride (CoPP) resulted in reduced segmented PMN migration into the alveolar space. In the CoPP group, segmented PMNs were also decreased intravascularly, and concordantly, mature and immature PMN populations were higher in the bone marrow. Inhibition of the enzyme by tin protoporphyrin-IX increased segmented and banded PMN migration into the bronchoalveolar lavage fluid with enhanced PMN release from the bone marrow and aggravated parameters of tissue inflammation. Oxidative burst activity was significantly higher in immature compared with mature PMNs. The chemokine stromal-derived factor-1 (SDF-1), which mediates homing of leukocytes into the bone marrow and is decreased in inflammation, was increased by CoPP. When SDF-1 was blocked by the specific antagonist AMD3100, HO-1 activation was no longer effective in curbing PMN trafficking to the inflamed lungs. In conclusion, we show evidence that the anti-inflammatory effects of HO-1 are largely mediated by inhibiting the release of segmented PMNs from the bone marrow rather than direct effects within the lung.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Cobalt (III) protoporphyrin-IX-chloride; Heme oxygenase-1; Neutrophil; Polymorphonuclear neutrophil granulocytes; Tin protoporphyrin-IX